Imidazole‐modified C6‐chitosan derivatives used to extract β‐sitosterol from edible oil samples with a microwave‐assisted solid phase extraction method. Issue 21 (8th September 2021) - Dai, Yunliang; Row, Kyung Ho
Abstract: β‐Sitosterol is a major bioactive constituent in plants with potent anticancer effects against many human cancer cells, but its bioavailability and therapeutic efficacy are limited by its poor solubility in water. In this study, C6 ‐imidazole chitosan, C6 ‐1‐methylimidazole chitosan, C6 ‐1‐ethylimidazole chitosan, C6 ‐1‐vinylimidazole chitosan, C6 ‐1‐allylimidazole chitosan, and C6 ‐1‐butylimidazole chitosan were prepared to extract β‐sitosterol from edible oil samples via ultrasonic‐assisted solid liquid extraction. The structures and properties of the newly synthesized products were characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, and elemental analysis. The extraction abilities of the derivatives were tested in the experiment with high‐performance liquid chromatography (limit of detection 0.21 μg/g and limit of quantification 0.67 μg/g), and the % relative standard deviation (<3.25%) and recovery values of the prepared chitosan derivatives toward β‐sitosterol (average: 100.20%) were acceptable. The spiked interday and intraday recoveries of β‐sitosterol were 102.60 ± 2.78 and 103.90 ± 3.04%, respectively. The actual amounts of β‐sitosterol extracted from three real samples using C6 ‐imidazole chitosan according to the solid phase extraction method were 3302.40, 901.70, and 2045.60 mg/kg for corn oil, olive oil, and pea oil, respectively.